La Cultura ambiental desde la participación ciudadana para el desarrollo de la conciencia crítica en la ciudadanía Lojana - Gonzaga Figueroa, Aurita Geovania (2018)
This article proposes an alternative on how to improve the environmental culture in people in order to obtain and live in a healthy environment. An essential element is to achieve in the social actors the development of their critical conscience so that the impacts of man on the environment diminish, to ensure the improvement of an environmental culture that provides the knowledge, skills and values necessary for personal and social transformation. The general objective of the research was to achieve the formation of an environmental culture in the "Gran 301Colombia" whole sale market merchants in Loja-Ecuador, through the integral management of solid waste generated in the area. The proposal was conceived from the methodology of research-action-participation, which is an effective way to guarantee the empowerment of processes of critical awareness development, active participation of those involved in the determination and solution of the problem and the elaboration of social projects initiatives that lead from the formation of an environmental culture to mitigate the environmental impacts from the leadership of citizenship. The evaluation of the results of the intervention project to contribute tothe formation of the environmental culture of the merchants, allowed the development of critical awareness of merchants about the problems of their environment, specifically the problem of poor solid waste management. From this perspective of research-action-participation, favorable changes were evidenced in terms of critical awareness, and the willingness to participate in tasks to solve current problems and prevent contamination of the sectors surrounding the market and environmental culture of the merchants to solve this deterioration is appreciated. Through this program, projects are established aimed at: recycling, bond application, environmental education based on the management and use of solid waste, selective storage, installation of a collection center and finally the promotion of the formation of an organization that exercise the use of solid waste